India’s Integrated Child Development Services programme; equity and extent of coverage in 2006 and 2016 - Chakrabarti, Suman; Raghunathan, Kalyani; Alderman, Harold; Menon, Purnima; Nguyen, Phuong Hong (World Health Organization, 2019)
Most research on the delivery of India’s Integrated Child Development Services programme in the period after the reforms has focused on performance in implementation of the programme by states,10 with limited evidence on individual and household uptake or use of the programme. In view of these gaps, we investigated changes in the use of the services over the continuum of care from pregnancy up to early childhood between 2006 and 2016. We assessed equity gaps and factors associated with use of services. Our analysis has policy implications for India, but also offers global lessons to other countries embarking on scalingup integrated programmes to address maternal and child health, nutrition and child development.